A Decision Support System for Selecting the Optimal Supplier Using the AHP and TOPSIS Methods with a Quantitative Approach in a Manufacturing Company - Maulia Rahman (Jurnal Info Sains : Informatika dan Sains, 2026)
Selecting the right supplier is a strategic decision for manufacturing companies as it has a direct impact on product quality, delivery timeliness and operational cost efficiency. In practice, many companies still select suppliers based on previous collaboration experience and subjective assessments without considering comprehensive and measurable criteria; consequently, the decisions made are prone to causing quality discrepancies and delivery delays. This study aims to design and implement a decision support system based on the integration of the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods to determine the weightings of criteria and rank supplier alternatives within a manufacturing company. The research employs a quantitative approach with a case study of five active suppliers selected via purposive sampling, using four evaluation criteria: price, quality, delivery punctuality and service; the data were processed using Microsoft Excel. The results of the study show that the quality criterion received the highest weight of 0.467 with a consistency ratio of 0.011, whilst the TOPSIS results ranked Supplier 3 as the best alternative with a preference value of 0.7454. These findings demonstrate that the integration of AHP and TOPSIS results in a more objective and measurable decision regarding supplier selection than an assessment based on a single criterion alone; it can therefore serve as a practical guide for procurement management in improving the effectiveness of supplier evaluation for raw materials in manufacturing companies.